PENGARUH EKSTRAK KELOPAK BUNGA ROSELLA TERHADAP PERTUMBUHAN CANDIDA ALBICANS DI RONGGA MULUT: EFFECT OF HIBISCUS SABDARIFFA TO THE GROWTH OF CANDIDA ALBICANS IN THE MOUTH - Poppy Andriany; Santi Chismirina; Faolyna (TALENTA, 2011)
The main composition of Rosella flower is flavonoid with gosipectin, anthocyanin and glucosid hibiskin as derivate of it. The pharmacologyc effect of these compounds are as anti fungus. The aim of this study was to explore a potential of Rosella calyx extract as anti fungus to Candida albicans. At first step of this study, prepared of Rosella calyx extract by using ethanol 96%, then this extract used for inhibited C. albicans by plate count control method. The result of study showed that the growth of C. albicans in 10% concentration only 16,66 CFU/ml compered to control which 150,00 CFU/ml. Meanwhile, there were not find the growth of C. albicans in 20%-100% concentrations. In conclusion, Rosella calyx extract have a potential to reduce the growth of C. albicans as candidiasis oral agent.